The Ghrelin/Growth Hormone Secretagogue Receptor System Is Involved in the Rapid and Sustained Antidepressant-Like Effect of Paeoniflorin - Zhang, Yuan; Zhu, Min-Zhen; Qin, Xi-He; Zeng, Yuan-Ning; Zhu, Xin-Hong (Frontiers in Neuroscience, 2021)
Major depressive disorder (MDD) is a debilitating mental illness affecting people worldwide. Although significant progress has been made in the development of therapeutic agents to treat this condition, fewer than half of all patients respond to currently available antidepressants, highlighting the urgent need for the development of new classes of antidepressant drugs. Here, we found that paeoniflorin (PF) produced rapid and sustained antidepressant-like effects in multiple mouse models of depression, including the forced swimming test and exposure to chronic mild stress (CMS). Moreover, PF decreased the bodyweight of mice without affecting food intake and glucose homeostasis, and also reduced the plasma levels of total ghrelin and the expression of ghrelin O-acyltransferase in the stomach; however, the plasma levels of ghrelin and the ghrelin/total ghrelin ratio were unaffected. Furthermore, PF significantly increased the expression of growth hormone secretagogue receptor 1 alpha (GHSR1α, encoded by the Ghsr gene) in the intestine, whereas the levels of GHSR1α in the brain were only marginally downregulated following subchronic PF treatment. Finally, the genetic deletion of Ghsr attenuated the antidepressant-like effects of PF in mice exposed to CMS. These results suggested that increased GHSR1α expression in the intestine mediates the antidepressant-like effects of PF. Understanding peripheral ghrelin/GHSR signaling may provide new insights for the screening of antidepressant drugs that produce fast-acting and sustained effects.